Evolution of local structure and superconductivity in CaFe2As2. (21st April 2021) - Pandeya, Ram Prakash; Pramanik, Arindam; Sakhya, Anup Pradhan; Mondal, Rajib; Yadav, A K; Jha, S N; Thamizhavel, A; Maiti, Kalobaran
Abstract: We investigate the evolution of the local structural parameters and their implication in unconventional superconductivity of 122 class of materials employing extended x-ray absorption fine structure studies. The spectral functions near the Fe K - and As K -absorption edges of CaFe2 As2 and its superconducting composition, CaFe1.9 Co0.1 As2 ( T c = 12 K) exhibit evidence of enhancement of Fe contributions near the Fermi level with Co substitution, which becomes more prominent at low temperatures indicating enhanced role of Fe in the electronic properties with doping. As–Fe and Fe–Fe bondlengths derived from the experimental data reveal evolution with temperature across the magneto-structural transition in the parent compound. The evolution of these parameters in Co-doped superconducting composition is similar to its parent compound although no magneto-structural transition is observed in this system. These results reveal an evidence of doping induced evolution to the proximity to critical behavior and/or strong nematic fluctuations which might be important for superconductivity in this system.